EKSPERIMENTASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN MURDER DENGAN BRAIN GYM TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DITINJAU DARI RESILIENSI MATEMATIS SISWA - Millentika Rachmadani; Dyah Ratri Aryuna; Riki Andriatna (Jurnal Karya Pendidikan Matematika, 2025)
This study aims to determine the effect of learning models on students' mathematical problem-solving abilities in terms of their mathematical resilience. The type of this research is quasi-experimental. The population of this study is the 11th-grade students of SMA Negeri 2 Sukoharjo for the 2023/2024 academic year, consisting of 4 11th-grade classes with a focus on Science and Mathematics. The sample used consists of two classes, with 36 students from class XI 2B as the experimental class and 35 students from class XI 1 as the control class, selected through cluster random sampling. Data collection was carried out using tests and questionnaires. The data analysis technique used is a two-way ANOVA with unequal cells, followed by a multiple comparison test using the Scheffé method. The research results show that the mathematical problem-solving ability of students who received the MURDER learning model with Brain Gym is better than that of students who received the MURDER learning model, both in general and at each level of mathematical resilience. Additionally, at each level of mathematical resilience, students show differences in mathematical problem-solving ability, both in general and in each learning model. In the MURDER learning model with Brain Gym, students with moderate mathematical resilience have better mathematical problem-solving ability than those with high and low resilience. Meanwhile, in the MURDER learning model, students with high mathematical resilience have better mathematical problem-solving ability than those with moderate and low resilience.